ANALISIS PENERAPAN STRATEGI BAURAN MANAJEMEN PEMASARAN TERHADAP PRODUK TABUNGAN UNTUK MENINGKATKAN JUMLAH NASABAH PENABUNG PADA BANK SYARIAH INDONESIA (BSI) - aulia gusvita; Syifaus Salwa (Jurnal Manajemen dan Bisnis (JMB), 2023)
Abstract Business  activities  are activities  that  require  serious  understanding,  starting  from planning what will be done, the implementation stage and the stage of monitoring a business being run. In running a business, the important task of marketers is to be able to provide what is needed by the community, both consumers and customers. In order for a business or business that is run to be successful, it would be nice to have an  appropriate  competitive  strategy.  This  study  aims  to  provide  a  study  and analysis of the marketing mix strategy (Marketing Mix) in the sharia perspective. The results of the study show that produ